Clinical Effectiveness of Peramivir in Comparison with Other Neuraminidase Inhibitors in Pediatric Influenza Patients. (22nd February 2012) - Hikita, Toshiyuki; Hikita, Hiroyuki; Hikita, Fusako; Hikita, Naoko; Hikita, Shizue
Abstract : The currently used antivirals in the treatment of influenza in Japan include amantadine, oseltamivir, zanamivir, laninamivir, and peramivir. We compared the efficacy of intravenous peramivir with that of other neuraminidase inhibitors for treating pediatric influenza. The present study included 223 influenza patients (≤18 years) who presented at the Hikita Pediatric Clinic between February and April 2011. We compared fever duration after starting treatment with antiviral drugs. Because inhalation drugs are difficult to use in <5-year-old patients and because of the potential adverse effects of oseltamivir in teenagers, we created two different age groups (<10-year-old group and 5–18-year-old group) to evaluate treatment results. In influenza A patients between 5 and 18 years old, the median fever duration after treatment with zanamivir was 2 days, compared with 1 day for peramivir (P = 0.0242 ). In influenza B patients between 5 and 18 years old, the median fever duration after treatment with laninamivir was 3 days, compared with 1 day for peramivir (P = 0.0097 ). We found no significant difference for any of the other combinations of drug/disease type/age groups. No adverse effects were observed with the antiviral drugs used. The results suggest that peramivir is very useful in pediatric influenza patients.